On the selective flotation of pentlandite from pyrrhotite in Sheba's Ridge ores - Mbonambi, Mduduzi Justice (Not Specified, 2023)
Metal sulphides are the raw material for most of the world's supplies of non-ferrous metals and can be considered one of the most important group of ore minerals. In the context of South Africa, the Bushveld Igneous Complex (BIC) sulphides play a very important role in that they are largely associated with the valuable platinum group elements (PGEs) and platinum group minerals (PGMs). Typically, the base metal sulphide (BMS) content in the BIC is comprised of pentlandite, pyrrhotite and chalcopyrite. Sheba's Ridge, one of the ore deposits found in the BIC, is exploited for its PGEs and PGMs. For typical PGE processing operations like the Merensky reef, the valuable PGEs and PGMs are associated with the base metal sulphides pentlandite, pyrrhotite and chalcopyrite. Unusually, in the case of the Sheba's Ridge ore, not all the sulphides contain associated PGEs and PGMs, and pyrrhotite has been observed to show little or no association. Therefore, this study was carried out to develop a methodology for the selective flotation of pentlandite from pyrrhotite using the polysaccharide depressants that are already in use in the flotation of BIC ores to control the naturally floating gangue minerals such as talc. Microflotation tests were conducted on a high grade Nkomati massive sulphide ore sample as a probe ore, to investigate the flotation response of pentlandite and pyrrhotite to four different chain length xanthate collectors (SEX, SNPX, SIBX and PAX) and to different types of polysaccharide depressants (guar, CMC and starch). The effect of oxygen addition and pH modification were also studied. Laboratory batch flotation tests were then carried out using the Sheba's Ridge ore, to evaluate the optimum reagent suite and flotation conditions determined in the microflotation tests. The results showed that using the different chain length xanthates or polysaccharide depressants on their own did not produce any pentlandite selectivity over pyrrhotite, but, when these reagents were used in conjunction with one another, some pentlandite selectivity was obtained. The best combination was found to be an intermediate chain length xanthate (SNPX) with guar depressant, where a balance between collector hydrophobicity and selectivity was obtained. Adjustment of the pH to 10, using lime instead of NaOH, together with artificial pre-oxidation showed further improvement in the selective flotation of pentlandite. This was attributed to the faster oxidation rate of pyrrhotite at these conditions, which led to selective depression of pyrrhotite while pentlandite floatability was maintained. The optimum reagent regime for pentlandite/pyrrhotite selectivity, as determined from the microflotation testwork using the Nkomati massive sulphide probe ore, was used as the basis of the batch flotation tests. The batch flotation tests represented a scale up of the microflotation tests, in terms of sample size (1 kg vs. 2 g) and were a closer representation of real operations, as silicate gangue minerals (e.g. talc) were present, as well as a froth phase. The variables that were found to be key in the microflotation testwork in terms of improving metallurgical performance for pentlandite selectivity were pH, collector and depressant type and dosage. These were the same variables identified as key in the batch flotation tests. However, the differences between these parameters were observed to be more subtle in the case of batch flotation tests compared to what was observed in the microflotation testwork. Nevertheless, it can be concluded that results from microflotation test work can used as a good basis to study of the interactions of different minerals in ores in a batch flotation system. Translating the results from microflotation testwork to batch flotation testwork was not so straight forward, and further work still needs to be done to prove that this can be done successfully. It was also found that there needs to be a synergistic interpretation of the interactions present in the reagent – mineral system. Finally, the study showed that the reagents used in flotation cannot be evaluated independently but rather a holistic approach needs to be employed.